Proposta de uma política de preservação digital para a Universidade Federal da Paraíba - Santos, Indalécia de Andrade dos (2021)
The preservation of digital objects in institutions, whether academic, research or other activities, is already a reality that cannot be denied. Increasingly, they are being created international standards and procedures to guide this action, which has aroused the interest of managers to preserve in the long run, your digital collections. The general objective of this work was to plan a proposal for a Digital Preservation Policy, in the context of the Federal University of Paraíba, taking into account the requirements, standards and guidelines established by national and international norms related to this subject. The path taken is the methodology of exploratory research exploratory research of an applied nature and a quanti-qualitative approach, based on bibliographic research, in addition to an empirical study with managers and professionals working in the Pro-Rectories; Archives, Libraries; Museum; Information Technology Superintendence (STI); Publishing company; Portal of Electronic Scientific Journals; Institutional Repository; UFPB TV; Information Coordination (CodeInfo) and Center Directors. The instrument for data collection was the Google Forms online questionnaire. After the project was submitted to and approved by the Human Research Ethics Committee, we sent the questionnaire individually to 50 servers. Results: 13 questionnaires were answered, which showed that the respondents the topic ‘digital preservation’ and realize that the University has been concerned about preserving its documentary legacy, although there is not yet a more incisive action in this direction. As for the unit responsible for the institution's digital preservation, the Central Archive was the one indicated by the majority, because, according to Resolution Nº 10/2019, those responsible for the management, procedures, support and digital procedures of the electronic process will be under the responsibility of the Central Archive and of the Information Technology Superintendence. As for the elaboration of the Digital Preservation Policy, we list the first procedures of a proposal to reach the final product. Regarding the preparation of the Digital Preservation Policy, we list the first procedures of a proposal to reach the final product. As a product of this research, we leave a Resolution Draft for the appreciation of the University. There is still a long way to go, and we leave as a product of this research a draft for the University's appreciation. We conclude that the few existing politics may contribute to institutions losing information, and the lack of awareness and funding is an aggravating factor for digital preservation. For this reason, managers need to institute guidelines, norms and standards in order to perpetuate the institutional, cultural and scientific memory.